Quality of life of ice hockey players after retirement due to concussions - Anna Gard; Niklas Lehto; Åsa Engström; Pashtun Shahim; Henrik Zetterberg; Kaj Blennow; Niklas Marklund; Yelverton Tegner (Concussion, 2020)
Background: Sports-related concussion (SRC) is increasingly recognized as a potential health problem in ice hockey. Quality of life (QoL) in players retiring due to SRC has not been thoroughly addr...